1967
DOI: 10.1002/anie.196709561
|View full text |Cite
|
Sign up to set email alerts
|

Photodimerization of Uracil Sensitized by Acetone

Abstract: 100 ml of pure CS2 at room temperature. The clear yellow solution, obtained by filtration from insoluble polymer, is acetone provides a further, mild method of specifically altering nucleic acids by photochemical methods. concentrated to 20 ml in a vacuum and then cooled at -3OOC for 12 h. The mother liquor is decanted from precipitated sulfur, and the latter is treated dropwise, with careful shaking, with sufficient pure CS2 (ca. 10 ml) to dissolve all the yellow s8 and leave behind only the characteristic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Both studies were designed to examine questions relevant to understanding the excited state(s) responsible for reaction and to gather kinetic data describing the various excited state processes that Ura undergoes when photolyzed in acetonitrile. The work of Lamola and Mittal (56) in 0.7 mM M solution indicted that two dimers were formed, while the work of Wagner and Bucheck (57) in 0.19 mM M solution suggested that all four isomers might be formed, based on analogy with results from the work of Krauch et al (48) on the photosensitized reaction of Ura in aqueous solution.…”
Section: Identification and Measurement Of The Relative Yields Of Thementioning
confidence: 86%
See 2 more Smart Citations
“…Both studies were designed to examine questions relevant to understanding the excited state(s) responsible for reaction and to gather kinetic data describing the various excited state processes that Ura undergoes when photolyzed in acetonitrile. The work of Lamola and Mittal (56) in 0.7 mM M solution indicted that two dimers were formed, while the work of Wagner and Bucheck (57) in 0.19 mM M solution suggested that all four isomers might be formed, based on analogy with results from the work of Krauch et al (48) on the photosensitized reaction of Ura in aqueous solution.…”
Section: Identification and Measurement Of The Relative Yields Of Thementioning
confidence: 86%
“…The work of Lamola and Mittal (56) in 0.7 m m solution indicted that two dimers were formed, while the work of Wagner and Bucheck (57) in 0.19 m m solution suggested that all four isomers might be formed, based on analogy with results from the work of Krauch et al. (48) on the photosensitized reaction of Ura in aqueous solution.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…B. Miller, ibid.,90, 1358 (1968). (15) For compound II, (ppm): H" 3.68, Hb 4.25, Hc 4.70, Ha 6.24, He 6.93, Hf 7.23, coupling constants Hz: b ~7, /ab = 1.9, < = 8.2, /of = 4.9, /be = 8.5, /be = 1.4, /ce = 2.0, Jit = 14.5; veo 2120, 2077, 2044 cm-1.Journal of the American Chemical Society / 91:25 j December3, 1969…”
mentioning
confidence: 99%
“…[21][22][23][24] All four CDs are formed after irradiation of a fluid solution (water or acetonitrile) and when the aqueous solution is acetone sensitized. [23][24][25][26] The trans-syn cyclodimers of U can be formed also by irradiation of denaturated DNA. 27 The molecular and crystal structure of cis-syn photodimer of U has been proposed by Adman.…”
Section: Fig 1 Four Cds Of Pyrimidine Nucleobasesmentioning
confidence: 99%